New methods of teaching English as a second language Uzbekistan State World Languages University - Berdiyeva Sitora, Abduqaxxorova Xadicha (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article examines modern methods of teaching English as a second language, highlighting key strategies such as listening to podcasts, watching movies with subtitles, vocabulary building, reading aloud, journaling, and regular speaking practice. Emphasis is placed on adapting to individual learning styles and creating a student centered environment that encourages communication and critical thinking.